1999
DOI: 10.1046/j.1365-2796.1999.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, gender and metabolic factors on endothelium‐dependent vasodilation: a population‐based study

Abstract: Abstract. Sarabi M, Millga Êrd J, Lind L (University Hospital, Uppsala, Sweden). Effects of age, gender and metabolic factors on endothelium-dependent vasodilation: a population-based study. J Intern Med 1999; 246: 265±274.Objectives. A progressive decline in endotheliumdependent vasodilation (EDV) in the human forearm with age has previously been reported. The aim of this study was to evaluate the interplay between age, gender and metabolic factors on EDV in healthy subjects in a population-based study. Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…A liberation of certain polyunsaturated fatty acids might also generate prostanoid-derived endothelium-generated constricting factors, such as thromboxane A2. Furthermore, also a modest rise in circulating glucose levels during MAT might attenuate EDV, as been shown in laboratory studies ) and in a population study (Sarabi et al 1999).…”
Section: Discussionmentioning
confidence: 57%
“…A liberation of certain polyunsaturated fatty acids might also generate prostanoid-derived endothelium-generated constricting factors, such as thromboxane A2. Furthermore, also a modest rise in circulating glucose levels during MAT might attenuate EDV, as been shown in laboratory studies ) and in a population study (Sarabi et al 1999).…”
Section: Discussionmentioning
confidence: 57%
“…It has been suggested that the increase in wall thickness with ageing is related to elevation in sympathetic outflow in the older individuals . Peak reactive hyperemic blood flow, an index of remodelling in resistance vessels in humans, is typically smaller in older individuals and independent of gender (Takeshita and Mark 1980;Sinoway et al 1986;Silber and Sinoway 1990;Silber et al 1991;Sarabi et al 1999). This suggests an age-dependent decrease in collective crosssectional area of peripheral resistance artery vascular bed and may infer the existence of some concentric arterial remodelling at this level of the vasculature.…”
Section: Impact Of Ageing On Vascular Structurementioning
confidence: 99%
“…Sex differences in FMD have been reported concomitantly with a greater postcuff hyperemia in premenopausal women compared with age-matched men (27,51). This effect has been explained by the positive influence of endogenous estrogens on the availability of NO (16), the principal vasodilator in shearmediated vasodilation (31).…”
Section: A Hormonal Milieu Effect On Flow-mediated Dilation?mentioning
confidence: 99%